Governance of Village Asset Management in Supporting the Development of a Successful Tourism Village: A Case Study of Wunut Village, Klaten Regency - Rosita Fatikasari; Rochman Hadi Mustofa (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
This study aims to analyze productive, transparent, and equitable village asset management practices through a case study of the Sumber Kamulyan Village-Owned Enterprise (BUMDes) in Wunut Village, Klaten Regency. Wunut Village went viral due to its success in managing Umbul Pelem Waterpark, which generated village income that not only increased the Village Original Income (PADes), but was also distributed directly to residents through the Holiday Allowance (THR) program and other social programs. The research method used was qualitative with a case study approach, involving in-depth interviews, observation, and documentation studies. The results of the study show that the successful management of village assets is supported by village deliberation mechanisms, community participation, optimal empowerment of local workers, equitable management of Micro, Small and Medium Enterprises (MSMEs), as well as innovation in facilities and digital promotion. This management has a significant impact on community welfare and strengthens the economic independence of the village. This research shows that village asset management oriented towards the principles of participation, transparency, and distributive justice can be a model of best practice in community-based economic and social development.